Effects of vulture exclusion on carrion consumption by facultative scavengers. Issue 5 (1st February 2018) - Hill, Jacob E.; DeVault, Travis L.; Beasley, James C.; Rhodes, Olin E.; Belant, Jerrold L.
Abstract: Vultures provide an essential ecosystem service through removal of carrion, but globally, many populations are collapsing and several species are threatened with extinction. Widespread declines in vulture populations could increase the availability of carrion to other organisms, but the ways facultative scavengers might respond to this increase have not been thoroughly explored. We aimed to determine whether facultative scavengers increase carrion consumption in the absence of vulture competition and whether they are capable of functionally replacing vultures in the removal of carrion biomass from the landscape. We experimentally excluded 65 rabbit carcasses from vultures during daylight hours and placed an additional 65 carcasses that were accessible to vultures in forested habitat in South Carolina, USA during summer (June–August). We used motion‐activated cameras to compare carrion use by facultative scavenging species between the experimental and control carcasses. Scavenging by facultative scavengers did not increase in the absence of competition with vultures. We found no difference in scavenger presence between control carcasses and those from which vultures were excluded. Eighty percent of carcasses from which vultures were excluded were not scavenged by vertebrates, compared to 5% of carcasses that were accessible to vultures. At the end of the 7‐day trials, there was a 10.1‐fold increase in the number of experimental carcasses that were not fully scavenged compared to controls. Facultative scavengers did not functionally replace vultures during summer in our study. This finding may have been influenced by the time of the year in which the study took place, the duration of the trials, and the spacing of carcass sites. Our results suggest that under the warm and humid conditions of our study, facultative scavengers would not compensate for loss of vultures. Carcasses would persist longer in the environment and consumption of carrion would likely shift from vertebrates to decomposers. Such changes could have substantial implications for disease transmission, nutrient cycling, and ecosystem functioning. Abstract : We excluded vultures from carcasses to measure the response of scavenging mammals. Mammals did not increase carrion consumption in the absence of vulture competition. Carcasses persisted longer when vultures were excluded, indicating that mammals would not functionally replace vultures as scavengers under these conditions.